Characterisation of the plasmodium falciparum Hsp40 chaperones and their partnerships with Hsp70 - Botha, Melissa (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2009)
Central to this research, 40 kDa Heat shock proteins (Hsp40s) are known to partner (or cochaperone) 70 kDa Heat shock proteins (Hsp70s), facilitating the selection and transfer of protein substrate to Hsp70 and the stimulation of the protein folding ability of Hsp70. Members of the diverse Hsp70-Hsp40 protein complement of Plasmodium falciparum have been implicated in the cytoprotection of this malaria parasite, and are thought to facilitate the protein folding, assembly and translocation tasks required by the parasite to commandeer the infected human erythrocyte subsequent to invasion. In particular, the parasite has evolved an expanded and specialised 43- member suite of Hsp40 proteins, 19 of which bear an identifiable export motif for secretion into the infected erythrocyte cytoplasm where they potentially interact with human Hsp70. Although type I Hsp40 proteins are representative of typical regulators of Hsp70 activity, only two of these proteins are apparent in the parasite's Hsp40 complement. These include a characteristic type I Hsp40 termed PfHsp40, and a larger, atypical type I Hsp40 termed Pfj1. Both Hsp40 proteins are predicted to be parasite-resident and are most likely to facilitate the co-chaperone regulation of the highly abundant and stress-inducible Hsp70 homolog, PfHsp70-I. In this work, the co-chaperone functionality of PfHsp40 and Pfj1 was elucidated using in vivo and in vitro assays. Purified recombinant PfHsp40 was shown to stimulate the ATPase activity of PfHsp70-I in in vitro single turnover and steady state ATPase assays, and co-operate with PfHsp70-I in in vitro aggregation suppression assays. In these in vitro assays, heterologous partnerships could be demonstrated between PfHsp70-I and the human Hsp40, Hsj1a, and human Hsp70 and PfHsp40, suggesting a common mode of Hsp70-Hsp40 interaction in the parasite and host organism. The functionality of the signature Hsp40 domain, the Jdomain, of Pfj1 was demonstrated by its ability to replace the equivalent domain of the A. tumefaciens Hsp40, Agt DnaJ, in interactions with the prokaryotic Hsp70, DnaK, in the thermosensitive dnaJ cbpA E. coli OD259 deletion strain. An H33Q mutation introduced into the invariant and crucial HPD tripeptide motif abrogated the functionality of the J-domain in the in vivo complementation system. These findings provide the first evidence for the conservation of the prototypical mode of J-domain based interaction of Hsp40 with Hsp70 in P. falciparum. Immunofluorescence staining revealed the localisation of PfHsp40 to the parasite cytoplasm, and Pfj1 to the parasite cytoplasm and nucleus in cultured intraerythrocytic stage P. falciparum parasites. PfHsp70-I was also shown to localise to the parasite cytoplasm and nucleus in these stages, consistent with the literature. Overall we propose that PfHsp40 and Pfj1 co-localise with and regulate the chaperone activity of PfHsp70-I in P. falciparum. This is the first study to identify and provide evidence for a functional Hsp70-Hsp40 partnership in P. falciparum, and provides a platform for future studies to elucidate the importance of these chaperone partnerships in the establishment and survival of the parasite in the intraerythrocytic-stages of development.
Keywords: Heat shock proteins; Plasmodium falciparum; Protein folding; Molecular chaperones; Malaria